Pengaruh entrepeneurial leadership, innovative work behavior , creative self efficacy terhadap employee performance dengan organizational culture sebagai variabel mediasi - Mawar Ratih Kusumawardani; Brahma Wahyu Kurniawan; Ahmad Faisal Saputro (Jurnal Manajemen Bisnis dan Kewirausahaan, 2026)
This study examines the influence of entrepreneurial leadership, innovative work behavior, and creative self-efficacy on employee performance, with organizational culture as a mediating variable. The research was conducted among MSME employees in Kediri City, specifically at Tenun Ikat Bandar. The number of respondents was 60 employees. The study adopted a quantitative, positivist approach, utilizing saturated sampling that encompassed all employees of Tenun Ikat Bandar. Data were collected using questionnaires and analyzed with Partial Least Squares (PLS). The novelty of this study lies in incorporating organizational culture as a mediating variable. The results show that entrepreneurial leadership, innovative work behavior and creative self-efficacy do influence employee performance. However, organizational culture does not mediate the effects of the three independent variables—entrepreneurial leadership, innovative work behavior, and creative self-efficacy—on employee performance. This research is limited by the use of questionnaires and not conducting in-depth interviews with all employees. As a result, there is less insight into the alignment between questionnaire responses and employees’ actual statements. Time constraints were another limitation of this study. Penelitian ini bertujuan untuk menganalisis pengaruh pengaruh entrepeneurial leadership, innovative work behavior , creative self efficacy terhadap employee performance dengan organizational culture sebagai variabel mediasi. Penelitian ini dilakukan pada karyawan UMKM di Kota Kediri yaitu Tenun Ikat Bandar. Jumlah responden pada penelitian ini adalah 60 karyawan. Metode penelitian menggunakan pendekatan kuantitatif dengan prinsip positivisme, melalui teknik sampel jenuh terhadap karyawan Tenun Ikat Bandar. Data dikumpulkan melalui kuisioner dan dianalisis menggunakan Partial Least Square (PLS). Kebaruan dalam penelitian ini adalah dengan memasukkan variabel organizational culture sebagai variabel mediasi. Hasil penelitian menunjukkan bahwa entrepeneurial leadership, innovative work behavior dan creative self efficacy memiliki pengaruh terhadap employee performance. Sedangkan organizational culture ternyata belum mampu memediasi ketiga variabel yaitu entrepeneurial leadership, innovative work behavior , creative self efficacy terhadap employee performance. Penelitian ini terbatas pada pengisian kuisioner dan kurangnya wawancara langsung dengan keseluruhan karyawan, sehingga belum mampu memberikan gambaran secara detail mengenai kesesuaian antara informasi yang didapatkan pada kuisioner dengan pernyataan dari karyawan. Selain itu keterbatasan waktu juga menjadi keterbatasan pada penelitian ini.